Invasive procedures and atraumatic care in pediatric nursing practice: nurses’ perceptions - Neto, Júlia; Fernandes, Rita; Andrade, Luísa; Fernandes, Ilda; Martins, Teresa; do Céu Barbieri-Figueiredo, Maria; Carvalho, Fernanda; Lima, Lígia (Frontiers in Pediatrics, 2025)
IntroductionInvasive procedures in pediatric nursing practice require a child-centered approach to minimize pain levels associated with manifestations of stress, anxiety, and long-term traumatic reactions.MethodThis cross-sectional study aimed at identifying nurses’ perception of stress, anxiety, and pain levels in children and adolescents (0–18 years) undergoing invasive procedures, and strategies used to minimize the associated distress. Based on a literature review, an online questionnaire was developed that evaluates the distress associated with frequent invasive procedures and strategies used to reduce discomfort.ResultsParticipants were 157 nurses who provided nursing care to children in all types of healthcare settings, such as hospitals and community health centers. Nurses evaluated lumbar puncture and catheter insertion as the procedures that caused more stress, anxiety, and pain in all age groups. ANOVA and post-hoc analyses indicate that nurses perceived adolescents as experiencing less stress than children in all the invasive procedures. Pediatric specialist nurses perceived a significantly higher total level of distress (an index that indicates stress, anxiety or pain in the whole group of procedures) compared to nurses with other specialties or generalist nurses, in all age groups. Non-pharmacological strategies were the most frequently used strategies used by nurses for minimizing distress in children, including distraction (51.2%), preparation (30.7%), and sensory techniques (14.6%). Pharmacological strategies, such as topical anesthetics and light sedation, were less frequently used.ConclusionThis study highlights the importance of specialized training and knowledge concerning strategies to reduce distress in pediatric invasive procedures, suggesting the need for more significant investment in education and support for nursing professionals to improve patient experience.